2017
DOI: 10.1016/j.actbio.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic peptide nanofibers repair cardiac tissue defect after myocardial infarction

Abstract: We present a synthetic bioactive peptide nanofiber system can enhance cardiac function and enhance cardiovascular regeneration after myocardial infarction (MI) without the addition of growth factors, stem cells or other biologically derived molecules. Current state of the art in cardiac repair after MI utilize at least one of the above mentioned biologically derived molecules, thus our approach is ground-breaking for cardiovascular therapy after MI. In this work, we showed that synthetic glycosaminoglycan (GAG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…Hence, one of the key points in the regeneration of infarcted myocardium, either by resident progenitor cells or cell therapy, is sufficient angiogenesis in the target zone. Formation of new vessels and an adequate blood supply to the affected area reduces cardiomyocyte apoptosis and the level of fibrosis [34,60,61]. Some studies support the idea of SAP hydrogels modified with angiogenic motifs that promote cardiac repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, one of the key points in the regeneration of infarcted myocardium, either by resident progenitor cells or cell therapy, is sufficient angiogenesis in the target zone. Formation of new vessels and an adequate blood supply to the affected area reduces cardiomyocyte apoptosis and the level of fibrosis [34,60,61]. Some studies support the idea of SAP hydrogels modified with angiogenic motifs that promote cardiac repair.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies support the idea of SAP hydrogels modified with angiogenic motifs that promote cardiac repair. One proposed mechanism was an increase in vascular density and vessel diameter [57,61]. N-acetyl-seryl-aspartyl-lysyl-proline (Ac-SDKP) is a tetrapeptide that has been well studied for improvement of the adverse effects of MI.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cells, growth factors, and other bio-activate elements have been applied to treat ischemic hearts [25][26][27]. Numerous functional/therapeutic peptides have been widely applied for cardiac disease research due to their advantages of easy synthesis, low toxicity, and rapid tissue absorption [24,28].…”
Section: Discussionmentioning
confidence: 99%
“…45 Further to these studies, Rufaihah et al demonstrated that a synthetic angiogenic peptide that mimics glycosaminoglycan (GAG), a fundamental component of the extracellular matrix, can induce recruitment of vascular cells and neovascularization in cardiovascular tissue post-MI. 46 ECG assessment showed that the injection of GAG NFs improved cardiac function at day 31 post-MI by preservation of left ventricular function when compared with saline as the control. The GAG mimetic peptide NFs also showed its inherent characteristic of inducing angiogenesis and vascular development via significant upregulation of vascular endothelial growth factor (VEGF) and angiopoietin-1 (Ang-1) without the addition of any growth factors or supplements in comparison to the saline control.…”
Section: Hydrogel-based Nanofibersmentioning
confidence: 94%
“…The GAG mimetic peptide NFs also showed its inherent characteristic of inducing angiogenesis and vascular development via significant upregulation of vascular endothelial growth factor (VEGF) and angiopoietin-1 (Ang-1) without the addition of any growth factors or supplements in comparison to the saline control. 46…”
Section: Hydrogel-based Nanofibersmentioning
confidence: 99%